Aerial observations of moving synchronized flow patterns in over-saturated city traffic. (January 2018) - Kaufmann, Stefan; Kerner, Boris S.; Rehborn, Hubert; Koller, Micha; Klenov, Sergey L.
Highlights: Moving synchronized flow patterns (MSPs) at the signal have been aerially observed. MSPs can propagate upstream through the complete road section or dissolve earlier. Two or several empirical MSPs can merge into a single MSP. MSPs can spontaneously emerge faraway upstream of the signal. A moving queue can spontaneously emerge within a MSP faraway upstream of the signal. Abstract: In this work, moving synchronized flow patterns (MSP) in empirical city traffic at signals have been observed which was predicted by Kerner (2013, 2014). The single vehicle data has been obtained through aerial observations. Based on this microscopic data, we have found trajectories for all vehicles together with vehicle speeds as functions of time and space. This has allowed us to find empirical MSPs in oversaturated city traffic as well as to perform microscopic analysis, that revealed the following empirical spatiotemporal features of MSPs: (i) MSPs emerge upstream of the queue at the signal and then they can propagate through the complete road section, (ii) merging of several MSPs into a single MSP, (iii) dissolving MSPs and (iv) spontaneous emerging of MSPs faraway upstream of the signal, (v) spontaneous emerging of moving queue within an MSP that is far away upstream of the signal. As a base for this work, we used an unmanned aerial vehicle (UAV) to record videos of inner city traffic situations and supervised tracking methods to gather the vehicle trajectories.